TUBERCULOSIS (Academicia Globe: Inderscience Research, 2022)
Infectious lesion of bacterial etiology. Do not develop a higher level of quality of human life. One risk group for tuberculosis accompanies all generations, possibly develops after infection of the human body with the tuberculous bacterium Mycobacterium or Bacillus Cocha.Diagnosis is established on the basis of analysis, determining minor improvements in the body.